LA GLOBALIZACIÓN DE LOS DERECHOS HUMANOS - Alvares García Junior, Armando (Revista Da Faculdade de Direito Da Universidade Federal de Minas Gerais, 2024)
Este artículo pretende, inicialmente, señalar el desarrollo histórico de la cláusula social y, posteriormente, analizar la incorporación de los derechos humanos y laborales asociados a esa cláusula en la realidad jurídica latinoamericana.
THE GLOBALIZATION OF HUMAN RIGHTS
This article intends, initially, to point out the historical development of the social clause and, later, to analyze the incorporation of human and labor rights associated to that clause in the Latin American juridical reality
Keywords: derechos humanos y laborales; Latinoamérica; Unión Europea; human and labour rights; Latin America; European Union